2002
DOI: 10.1111/j.1151-2916.2002.tb00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Development of Natural Hydroxyapatite Originated from Fish‐Bone Waste through Heat Treatment

Abstract: The morphologic and microstructural development of natural fish bone through heat treatment is examined in view of fish-waste management and as a possible route for hydroxyapatite ceramics. Fish bone heated at temperatures <1300°C maintains a porous structure, with a sintered wall and a major crystalline phase of hydroxyapatite. Fish-originated ceramics are potentially useful as bioactive media as well as for environmentally compatible materials. P. Ducheyne-contributing editorManuscript No. 188335.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
85
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(94 citation statements)
references
References 8 publications
6
85
0
3
Order By: Relevance
“…Extraction of HAp from the bio-wastes is a biologically safe (no foreign chemicals are utilized) and economically desirable process especially with the increasing world demand of HAp bioceramics. Many bio-wastes have been exploited for such purpose, for instance fish bones [24], bovine bones [25] and bones and teeth of pig [26]. Unfortunately, it was reported that most of the carbonate groups present in the carbonated hydroxyapatite are eliminated by heating which affects the biological properties of the obtained apatite extracted by the thermal process [22,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of HAp from the bio-wastes is a biologically safe (no foreign chemicals are utilized) and economically desirable process especially with the increasing world demand of HAp bioceramics. Many bio-wastes have been exploited for such purpose, for instance fish bones [24], bovine bones [25] and bones and teeth of pig [26]. Unfortunately, it was reported that most of the carbonate groups present in the carbonated hydroxyapatite are eliminated by heating which affects the biological properties of the obtained apatite extracted by the thermal process [22,27].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the PLPW has been utilized to pluck the collagen and other organic compounds out the bovine bones leaving the desired natural apatite. The third process utilized in this study is direct heating of the bovine bone to remove the organic compounds which can be thermally eliminated [24][25][26]36].…”
Section: Introductionmentioning
confidence: 99%
“…Bioceramics derived from natural sources like coral [1], fish bone [2], oyster shell [3] and bovine bone, etc. [4,5] inherit some of the properties of the raw materials such as pore structure, carbonate content and minor concentration of trace elements etc.…”
Section: Introductionmentioning
confidence: 99%
“…porcine bone (Im, Chung, Lim, Choung, & Hong, 2007;Janus, Faryna, Haberko, Rakowska, & Panz, 2008;Sobczak et al, 2009), bovine bone (Barakat et al, 2008;Mezahi et al, 2009;Sobczak et al, 2009;Taniguchi et al, 1999;Tsai et al, 2010;Ueno et al, 1983), chicken bone (Kim, Rey, & Glimcher, 1996), and fish bone and scales (Mondal, Mondal, Dey, & Mukhopadhyay, 2012;Ozawa & Suzuki, 2002). In addition, it was reported that the characteristics of HA derived from biowastes could be altered by various conditions, such as the types of osseous tissue (i.e.…”
Section: Introductionmentioning
confidence: 99%